Metagenomic insights into antibiotic resistance-related changes in microbial communities, resistome and mobilome under a modified A2/O treatment process for hospital sewage. Issue 1 (February 2023) - Yuan, Yumeng; Zeng, Mi; Sun, Jiayu; Li, Xin; Yao, Fen; Shafiq, Muhammad; Guo, Xiaoling; Wang, Meimei; Lu, Tao; Wong, Nai-Kei; Li, Adela Jing; Jiao, Xiaoyang
Abstract: Sewage treatment is crucial to environmental security by restricting the spread of antimicrobial resistance (AMR). However, there remains little consensus on genome-guided approaches to evaluating treatment efficacy, particularly with respect to the bacterial resistome and mobilome. Here, we present the first comprehensive metagenomic evidence for AMR-related changes in the bacterial resistome and mobilome in hospital sewage before and after treatment as modified by an anaerobic-anoxic-oxic (A 2 /O) process. Key factors involved in AMR dissemination including diversities of microbial communities, antibiotic resistance genes (ARGs), and mobile genetic elements (MGEs) in untreated and treated sewage were analyzed by metagenomic and bioinformatic methods. Sixteen out of the most common 20 bacterial species were reduced, with Enterococcus faecalis showing the highest clearance rate (88.46%). Of the highest occurring 20 ARGs, five types of ARGs significantly declined ( p < 0.01), including crp, tetQ, ermF, aadA24, and catB3, whereas the other ARGs such as aac, aph, VEB-3, mphE, msrE, sul1, GES-6, qacH, OXA-3, and ereA increased in the treated sewage ( p < 0.01). Of the top 20 MGEs, only five types were reduced, while the other MGEs were increased by treatment ( p < 0.01). Network analysis further reveals that connections between bacteria and ARGs, and connections between MGEs and ARGs were weakened significantly under A 2 /O. Overall, our work demonstrates the relevance and utility of resistome and mobilome as assessment criteria in AMR monitoring panels for more comprehensive evaluation of the effectiveness of sewage treatment against the spread of AMR. Graphical Abstract: ga1 Highlights: Sixteen out of the top 20 bacteria were significantly reduced after treatment. Correlation between bacteria and ARGs, ARGs and MGEs were significantly reduced. The analysis of resistome and mobilome in effluent offer evidence of AMR spread.